Different intracellular polyamine concentrations underlie the difference in the inward rectifier K(+) currents in atria and ventricles of the guinea-pig heart - Yan, Ding-Hong (Blackwell Science Inc, 2005)
The outward component of the strong inward rectifier potassium current, I(K1), is significantly larger in ventricles than in atria of the heart, resulting in faster repolarization at the final phase of the action potential in ventricles. However, the underlying mechanism of the difference in I(K1) remains poorly understood. I(K1) channels are composed of subunits from the Kir2 subfamily, and I(K1) amplitude is determined by the voltage-dependent blockade of the channel by the intracellular polyamines spermine and spermidine, and by Mg(2+). Using a perforated patch-clamp method, which minimizes changes in the intracellular polyamine and Mg(2+) concentrations, we detected repolarization-induced outward I(K1) transients, which are caused by competition between Mg(2+) and spermine to block the channel, in ventricular but not in atrial myocytes from guinea-pig heart. The contribution of the Kir2.3 subunit to the I(K1) channel was found to be minor in the guinea-pig heart, because the activation time course of the Kir2.3 currents was ∼10-fold slower than those of I(K1), and the marked external pH sensitivity of the Kir2.3 currents was not found in I(K1). Both the Kir2.1 and Kir2.2 currents recorded from inside-out patches exhibited outward transients similar to those of ventricular I(K1) in the presence of 5–10 μm spermine and 0.6–1.1 mm Mg(2+), and their amplitudes were diminished by increasing the spermine or spermidine concentrations. The total and free polyamine concentrations in guinea-pig cardiac tissues were higher in atria than ventricles. These results strongly suggest that different intracellular polyamine concentrations are responsible for the difference in atrial and ventricular I(K1) of the guinea-pig heart.